Mixed-mode electro-optical operation of Ge2Sb2Te5 nanoscale crossbar devices - Rodriguez-Hernandez, G; Hosseini, P; Ríos, C; Wright, C; Bhaskaran, H (Wiley, 2017)
The use of phase-change materials for a range of exciting new optoelectronic applications from artificial retinas to ultrahigh-resolution displays requires a thorough understanding of how these materials perform under a combination of optical and electrical stimuli. This study reports for the first time the complex link between the electronic and optical properties in real-world crossbar nanoscale devices constructed by confining a thin layer of Ge 2 Sb 2 Te 5 between transparent indium tin oxide electrodes, forming an optical nanocavity. A novel proof-of-concept device that can be operated by a combination of optical and electrical stimuli is presented, leading the way for the development of further applications based on mixed-mode electro-optical operation.